2020
DOI: 10.9734/or/2020/v13i230164
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Visual Outcomes between Panretinal Photocoagulation and Panretinal Photocoagulation Plus Intravitreal Bevacizumab in Proliferative Diabetic Retinopathy Patients Treated at Northen Zonal Hospital

Abstract: Introduction: Diabetic retinopathy is one of the rigorous microvascular complications of diabetes mellitus is the significant cause of visual impairment and consequently blindness affecting about 36% of the diabetic population. Diabetic macular edema (DME) and proliferative diabetic retinopathy (PDR) are two prime manifestations of DR that are responsible for visual morbidity. The basis of the treatment in PDR is Laser photocoagulation as accomplished by Diabetic retinopathy treatment study (DRS) and early tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…Though multiple reinjections are required to maintain a visual improvement some patients have regression of retinal neovessels. Similar to our study, Darabe, F et al, 13 concluded that IVB is a safe and effective adjunctive treatment to PRP in the short term. PRP plus IVB is associated with a higher and early rate of regression of active NVs than PRP alone in patients with PDR.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Though multiple reinjections are required to maintain a visual improvement some patients have regression of retinal neovessels. Similar to our study, Darabe, F et al, 13 concluded that IVB is a safe and effective adjunctive treatment to PRP in the short term. PRP plus IVB is associated with a higher and early rate of regression of active NVs than PRP alone in patients with PDR.…”
Section: Resultssupporting
confidence: 92%
“…Whereas in the study performed by Rebbeca et al, 12 the male (%) and female (%) in group-A was 58.25 and 41.75, respectively while 62.96 and 37.04 in group B respectively. Further, in the investigation of Darabe, F et al, 13 He, F et al, 14 and Choi W et al, 15 no gender was considered as a prominent isolative factor. Lastly, in the study of Obeid A et al, 16 the observed male: female ratio was 31:28.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations